Orthopaedic Management of Concurrent Ulna and Metacarpal Fractures in a Duck (Anas platyrhynchos domesticus) - Sangeet Rana (Journal of Applied Veterinary Science And Technology, 2026)
Background: Guarded prognoses are frequently associated with traumatic injuries in ducks due to their delicate skeletal structures, limited musculature, and high susceptibility to stress and shock. Complexity in treatment is significantly increased when wing fractures occur concurrently with severe limb damage, particularly in emergency presentations where a comprehensive diagnostic work-up may be constrained.  Purpose: Described in this report are the clinical findings and surgical management of a domestic duck presented with simultaneous fractures of the ulna and major metacarpal bone, accompanied by a severely devitalized hindlimb resulting from a canine inflicted injury. Case(s): A female Anas platyrhynchos domesticus was presented in critical condition, exhibiting an inability to stand or utilize the left wing. Identified during clinical examination were abnormal angulation, swelling, and crepitus in the wing, while extensive soft tissue devitalization was noted in the left hindlimb. Confirmation of complete fractures of the ulna and major metacarpal bone, alongside an intact radius and significant disruption of hindlimb structures, was achieved via radiography. Case Management: Anesthesia was induced using a combination of xylazine and ketamine and maintained with isoflurane. Stabilization of the major metacarpal fracture was performed using a normograde intramedullary pin fashioned from a 14 gauge cannula stylet, while the ulnar fracture was managed with a unilateral type I linear external skeletal fixator reinforced with epoxy resin. Owing to irreversible tissue damage, amputation of the left hindlimb was necessitated. Postoperative care encompassed the administration of oral antibiotics, supportive supplementation, and routine wound management. Conclusion: Technically achievable in ducks are combined fracture repair and limb amputation; however, the severity of trauma and associated physiological shock may still result in poor survival outcomes despite appropriate surgical intervention.